Chemotherapy Combined With Recombinant Human Endostatin (Endostar) Significantly Improves the Progression-Free Survival of Stage IV Soft Tissue Sarcomas - Liao, Zhichao; Zhang, Chao; Yang, Tielong; Liu, Haotian; Yang, Songwei; Li, Ting; Xing, Ruwei; Teng, Sheng; Yang, Yun; Zhao, Jun; Zhao, Gang; Bai, Xu; et al. (Frontiers in Oncology, 2022)
Purpose: Our previously study showed that recombinant human endostatin (Endostar) combined with chemotherapy had significant activity to increase the mPFS in patients with advanced sarcomas with tolerable side effects. However, the small cohort size and short follow-up time made it difficult to screen sensitive sarcoma subtypes and determine whether there is an overall survival benefit. With the largest sarcoma cohort to our knowledge, we try to confirm the efficacy and safety of chemotherapy combined with Endostar in stage IV sarcomas, with the specific purpose of finding out the sensitive sarcoma types for this combined treatment. Methods: After the exclusion of ineligible patients, 156 patients with stage IV bone and soft tissue sarcomas were included in this study according to the inclusion criteria. Results: By the end of follow-up, the ORR was 10.7% (9/84) vs 1.4% (1/72) (p=0.041), the DCR was 26.2% (22/84) vs 5.6% (4/72) (p=0.001) in the combined group and chemotherapy group, respectively. The mPFS of combined group was significantly longer than the chemotherapy group (10.42 vs 6.87 months, p=0.003). The mOS were 26.84 months and 23.56 months, without significant difference (p= 0.481). In osteogenic sarcoma, there was no statistically significant difference in the mPFS between the two groups (p=0.59), while in the soft tissue sarcoma, the mPFS in the combined group was significantly higher than that of the chemotherapy group (11.27 vs 8.05 months, p=0.004). Specifically, undifferentiated polymorphic sarcoma (UPS) was the possible sarcoma subtypes that benefited from the combined therapy. For the 38 UPS patients (28 patients in the combined group and 10 patients in the chemotherapy group), the mPFS in the combined group was up to 14.88 months, while it was only 7.1 months in the chemotherapy group, with a significant difference (p=0.006).. The most common adverse events in the combined group were myelosuppression, gastrointestinal reactions and abnormal liver function, without significant difference in two groups. Conclusion: Chemotherapy plus Endostar could prolong mPFS and improve ORR and DCR in patients with stage IV soft tissue sarcoma, suggesting that the combined therapy could improve the patient prognosis in soft tissue sarcomas, especially the UPS patients.